2014
DOI: 10.1186/1756-3305-7-378
|View full text |Cite
|
Sign up to set email alerts
|

Sodalis glossinidius prevalence and trypanosome presence in tsetse from Luambe National Park, Zambia

Abstract: BackgroundTsetse flies are the biological vectors of African trypanosomes, the causative agents of sleeping sickness in humans and nagana in animals. The tsetse endosymbiont Sodalis glossinidius has been suggested to play a role in tsetse susceptibility to infection. Here we investigate the prevalence of African trypanosomes within tsetse from the Luambe National Park, Zambia and if there is an association between S. glossinidius and presence of trypanosomes within the tsetse examined.MethodsTsetse representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
33
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 43 publications
13
33
8
Order By: Relevance
“…The Sodalis infection prevalence observed in the present study are comparable with circa 20% reported in other morsitans group tsetse (Dennis et al, 2014;Wamwiri et al, 2013) but markedly lower than those reported in species such as Glossina palpalis palpalis (Farikou et al, 2010) with infection rate of about 55%. Previous workers also report no significant difference in infection prevalence between male and female flies (Dennis et al, 2014), indicating that our results using male flies only could be a true reflection of the population infection status.…”
Section: Wolbachia Sodalis Sghv and Trypanosome Infectionsupporting
confidence: 83%
See 4 more Smart Citations
“…The Sodalis infection prevalence observed in the present study are comparable with circa 20% reported in other morsitans group tsetse (Dennis et al, 2014;Wamwiri et al, 2013) but markedly lower than those reported in species such as Glossina palpalis palpalis (Farikou et al, 2010) with infection rate of about 55%. Previous workers also report no significant difference in infection prevalence between male and female flies (Dennis et al, 2014), indicating that our results using male flies only could be a true reflection of the population infection status.…”
Section: Wolbachia Sodalis Sghv and Trypanosome Infectionsupporting
confidence: 83%
“…While these results are consistent with the observations in G. pallidipes and G. palpalis palpalis (Farikou et al, 2010;Wamwiri et al, 2013), they are contradictory to the conclusions of Dennis et al (2014) who found no association between infection with Sodalis and midgut trypanosome infections in Glossina brevipalpis, G. morsitans morsitans and G. pallidipes. The dynamics of trypanosome infection are complex and may be influenced by composition of the microbiome .…”
Section: Associations Of Trypanosome Infection and Tsetse Microbiomecontrasting
confidence: 78%
See 3 more Smart Citations